Cultural management in family business - Patricia Amelia Tomei; Patrícia Jaguaribe Ferrari (BBR: Brazilian Business Review)
This article's main goal is to analyze how the evolution of organizational culture can impact business performance. A theoretical framework was developed based on a review of the literature relating to organizational culture and family business succession management models. A single case study methodology was adopted based on primary and secondary data obtained through documentary research, participant observation and interviews at Guapo Loco, a Brazilian chain of Mexican restaurants / fun bars, which is a family company and was founded in Rio de Janeiro in 1996. We focused on its leader's trajectory and its implications for the life cycle of the family business, the founder¿s dream and vision, succession and cultural management difficulties. We conclude that it is possible for an organization to become trapped by its cultural formation. We will see that as it reaches maturity, the organizational, family and shareholder dimensions need to adapt in a similar fashion. At this stage, the organizational culture may become dysfunctional, jeopardizing the organization's survival.